Ecological Transformation of the Economy – Inevitable Necessity - Ivanova, Vania (Research Papers, 2019)
The focus of this research is on building a new model of socio-ecological development. The aim of the project is to demonstrate the need for environmental transformation and the need for a change in economic policies in support of a new type of economy geared towards ensuring a new quality of life and environmental care. Making environmental barriers a lever for economic development conducive to economic activity, employment and income growth as well as mitigating social imbalances are seen as a potential chance in today’s economic situation. Methods of analysis and synthesis were used, an interdisciplinary synergistic approach based entirely on secondary research.